Wireless Charging System With a Non-conventional Compensation Topology for Electric Vehicles and Other Applications - Ruben Barros Godoy; Emilio Tanowe Maddalena; Glauber de Freitas Lima; Luiz Fernando Ferrari; Vitor Leandro Vieira Torres; João Onofre Pereira Pinto (Eletrônica de Potência)
The proposed paper presents a complete 500W, universal input, wireless electric vehicle battery charging system using a non- conventional compensation topology, LSPS. An algorithm to compensate Loosely Coupled Inductive Power Transfer (LCIPT) systems with such topology is explained. The design and implementation of each power converter, as well as the coils manufacturing process, is briefly covered. Experimental results are shown to validate the expected system behavior.